Ecological implications of motor oil pollution: Earthworm survival and soil health. (June 2015) - Ramadass, Kavitha; Megharaj, Mallavarapu; Venkateswarlu, Kadiyala; Naidu, Ravi
Abstract: The nontarget effects of fresh and used motor oil were studied in a soil test system involving such criteria as earthworm survival, response of soil dehydrogenase and urease, and nitrification. When earthworms were exposed to motor oil-contaminated soil for 4 weeks, the observed median lethal concentrations (LC50 ) were 40.33 and 3.88 g kg −1 soil for fresh and used oil, respectively. Only fresh motor oil application increased earthworms' body weight even at the higher dose of 19 g kg −1 soil. Gas chromatography/mass spectrometry revealed that used motor oil contained more of aromatic hydrocarbons and heavy metals than fresh oil. This disparity in the chemical composition might be the factor responsible for the significant toxicity of used motor oil towards earthworms. Activities of soil dehydrogenase and urease were significantly enhanced in presence of both the motor oils, while there was a significant inhibition in nitrification by the used motor oil even at a low concentration of 0.2 g kg −1 soil. This study clearly demonstrated that earthworm survival and nitrification could serve as suitable indices to assess motor oil pollution in soil. Highlights: Used motor oil was significantly toxic to earthworm in soil. Total petroleum hydrocarbon loss was pronounced from soil containing worms. Chemical constituents formed in used oil are responsible for the greater toxicity. Lower concentrations of used oil increased soil dehydrogenase and urease. Soil nitrification was adversely affected by used oil pollution.